Decidualization of the canine uterus: From early until late gestational in vivo morphological observations, and functional characterization of immortalized canine uterine stromal cell lines. (15th November 2016) - Graubner, FR; Reichler, IM; Rahman, NA; Payan‐Carreira, R; Boos, A; Kowalewski, MP
Contents: The apparent lack of classical mechanisms for maternal recognition of pregnancy is one of the most intriguing features of canine reproduction. Consequently, similar levels of circulating luteal steroids are observed in pregnant and non‐pregnant dogs. However, the early pre‐implantation canine embryo locally modulates uterine responses to its presence, facilitating the successful onset of pregnancy. As a part of this interaction, the canine uterus undergoes a species‐specific decidualization. Maternal stroma‐derived decidual cells develop, the only cells of the canine placenta expressing progesterone receptor (PGR). There exists an acute need for an in vitro stable cell line model for canine decidualization. Therefore, herein our goal was to establish, immortalize and characterize such a cell line. We immortalized three monolayer dog uterine stromal (DUS) cell lines by stably transfecting them with SV40Tag oncogene. Cells retained their mesenchymal character for over 30 passages, as evidenced by VIMENTIN staining. Genomic incorporation of the SV40Tag protein was confirmed by immunofluorescence and Western blot analyses. Cells submitted to a classical in vitro decidualization protocol (N6, 2′‐O‐dibutyryladenosine‐3′, 5′‐cyclic monophosphate) revealed upregulated gene levels of selected major decidualization markers ( e.g . PRLR, PGR, IGF1, PTGES ). Additionally, the basic decidualization capability of PGE2 was demonstrated, revealing increased levels of, for example, PGR and PRLR gene expression, thereby implying its involvement in the progesterone‐dependent decidualization in the canine uterus. In summary, our in vitro model with immortalized DUS cell line could serve as an ideal and unique model to study the underlying molecular and endocrine mechanisms of canine decidualization.